Smugglers and Patriots Boston Merchants and the Advent of the American Revolution - Tyler, John W. (Northeastern University Press, 2019)
No single element of Boston's revolutionary history is of greater consequence than the reactions of the town's merchants to changing British mercantile policies. Under John Tyler's fine lens the special business interests of powerful individuals within this group are more clearly delineated and, as a consequence, their political behavior is better understood. Through ingenious research into business ledgers and insurance records John Tyler has been able to identify specific members of this elusive group for the first time and observe their political conduct for a decade and a half prior to the American Revolution. Originally published by Northeastern University Press in 1986. With a new foreword by William M. Fowler, Jr.